Diabetes, pre-diabetes and their risk factors in Malta: a study profile of national cross-sectional prevalence study. (2016) - Cuschieri, S.; Vassallo, J.; Calleja, N.; Pace, N.; Mamo, J.
Abstract : Background: Type 2 diabetes mellitus constitutes a global epidemic and a major burden on health care systems across the world. Prevention of this disease is essential, and the development of effective prevention strategies requires validated information on the disease burden and the risk factors. Embarking on a nationally representative cross-sectional study is challenging and costly. Few countries undertake this process regularly, if at all. Method: This paper sets out the evidence-based protocol of a recent cross-sectional study that was conducted in Malta. Data collection took place from November 2014 to January 2016. Results: This study presents up-to-date national data on diabetes and its risk factors (such as obesity, smoking, physical activity and alcohol intake) that will soon be publicly available. Conclusion: This protocol was compiled so that the study can be replicated in other countries. The protocol contains step-by-step descriptions of the study design, including details on the population sampling, the permissions required and the validated measurement tools used.